Decolonizing the Mind. Ethiopia in ‘Memorie di una principessa etiope’ by Martha Nasibù - Barbara Małgorzata Kornacka (Incontri: Rivista Europea di Studi Italiani)
The paper analyses in what way the novel contributes to the decolonization of the mind. The writer, being herself Ethiopian from an aristocratic family, having studied in Europe and in the USA, has a wide and unprejudiced perspective. In her novel she deconstructs the historical hierarchy of the Occident (superior) and the Orient (inferior). From the narrator’s point of view, a double subaltern subject, being both female and black, the Ethiopians are cultured, noble and superior. The Occidentals, the Italians, in contrast are often represented as rude, violent and insensible, thus inferior.